2003
DOI: 10.1029/2003gl017633
|View full text |Cite
|
Sign up to set email alerts
|

The role of marsh‐dominated heterotrophic continental margins in transport of CO2 between the atmosphere, the land‐sea interface and the ocean

Abstract: Recent air‐to‐sea CO2 flux measurements at several major continental shelves suggest that shelves may act as a one‐way pump and absorb atmospheric CO2 into the ocean. The U.S. South Atlantic Bight (SAB) contrasts these findings in that it acts as a source of CO2 to the atmosphere while simultaneously exporting dissolved inorganic carbon (DIC) to the open ocean. The shelf‐wide heterotrophy and carbon exports in the SAB are subsidized by the export of organic carbon from the abundant intertidal marshes, which ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
135
2

Year Published

2004
2004
2017
2017

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 135 publications
(142 citation statements)
references
References 26 publications
5
135
2
Order By: Relevance
“…Inversely, intense benthic and planktonic CR at high tide in the flat would not necessarily immediately generate an equivalent degassing of CO 2 to the atmosphere, with some of the CO 2 remaining in solution and being exported laterally with the subsequent ebb tide. Such CO 2 outwelling from intertidal systems to adjacent creeks and bays has been observed in many tidal wetlands (Cai et al, 2003;Wang and Cai, 2004;Borges et al, 2003). The September 2007 measurements at Station 2 in the inner part of the flat provide a first and relatively simple scheme for conceptualising NEE dynamics in relation to NEP at the different phases of the day and the tide.…”
Section: Wind Direction and Zostera Noltii Covermentioning
confidence: 79%
“…Inversely, intense benthic and planktonic CR at high tide in the flat would not necessarily immediately generate an equivalent degassing of CO 2 to the atmosphere, with some of the CO 2 remaining in solution and being exported laterally with the subsequent ebb tide. Such CO 2 outwelling from intertidal systems to adjacent creeks and bays has been observed in many tidal wetlands (Cai et al, 2003;Wang and Cai, 2004;Borges et al, 2003). The September 2007 measurements at Station 2 in the inner part of the flat provide a first and relatively simple scheme for conceptualising NEE dynamics in relation to NEP at the different phases of the day and the tide.…”
Section: Wind Direction and Zostera Noltii Covermentioning
confidence: 79%
“…Based on observations from the East China Sea, Tsunogai et al (1999) proposed the existence of a global continental shelf pump that theoretically could remove as much as 1 Gt C/yr (+83×10 12 mol C/yr) from the atmosphere, which corresponds to about 15% of the CO 2 released annually from human activities. Opposed to these observations, a recent study from the South Atlantic Bight indicates that this continental shelf region acts as a significant source of CO 2 to the atmosphere (Cai et al, 2003). The authors suggested that extensive export and remineralization of organic matter from nearby salt-marshes could account for this observed flux.…”
Section: Air and Surface Ocean Systemmentioning
confidence: 84%
“…In recent years, detailed field studies of CO 2 fluxes have taken place in a few areas, such as the East China Sea, northwest European Shelf, Baltic Sea, and North Sea (Chen and Wang, 1999;Frankignoulle and Borges, 2001;Borges and Frankignoulle, 2002;Borges et al, 2003). However, only limited information about these CO 2 fluxes is available on a global scale (Liu et al, 2000b, a;Cai et al, 2003;Chen et al, 2003;Omstedt et al, 2009;Norman et al, 2013b).…”
Section: G Parard Et Al: Air-sea Co 2 Fluxesmentioning
confidence: 99%